QARAQALPAQSTAN JAǴDAYÍNDA POPULUS ARIANA DODENIŃ BIO-EKOLOGIYALÍQ ÓZGESHELIKLERI - Baltabaev, M.T.; Abilova, A. (SCIENCE and SOCIETY, 2025)
This article examines the biological and ecological characteristics of Populus ariana Dode. under the conditions of Karakalpakstan. The study analyzes the vegetation period, flowering and fruiting processes, adaptation to soil and climatic conditions, as well as the possibilities of vegetative and seed propagation. The P. ariana species is distinguished by its resistance to soil salinity and moisture deficiency, making it a valuable material for landscaping and afforestation.